Transplantational and specific antitumor immunity in retrospective view: new models based on transgenesis of individual chains of T-cell receptor - D. B. Kazanskiy; Yu. Yu. Silaeva; A. A. Kalinina; M. A. Zamkova; L. M. Khromykh; N. A. Persiyantseva; L. Kh. Dzholokhava (Успехи молекулярной онкологии, 2016)
Findings in experimental oncology in beginning of last century and subsequent achievements of genetics of tissue compatibility resulted in divergence of transplantational immunology and oncoimmunology. However, central achievements of both scientific fields are based on unified phenomenon of interaction between T-cell receptor (TCR) and histocompatibility molecules. In this review we describe the history of ideas, achievements and unique experience of the team of the Laboratory of Regulatory Mechanisms in Immunity at Scientific Research Institute of Carcinogenesis, N.N. Blokhin Russian Cancer Research Center for all time of existence. This experience shows that efficiency of immunological defense including immunological surveillance are critically influenced by T-cell receptor repertoire. Transgenesis of individual chains of TCR is one of possible means to manage T-cell repertoire. Functional outcomes of transgenesis may be different due to diverse extent of dependence of α- and β-chains expression on the rules of allelic exclusion. Expression of transgenic β-chains results in the expansion of TCR repertoire diversity. Expression of β-chains is under strong control by allelic exclusion, resulting in formation of repertoire bearing mainly invariant transgenic β-chain pared with different α-chains and overall narrowing of repertoire. Earlier, we cloned genes encoding α- and β-chains of TCR of CD8+ memory cells specific to histocompatibility molecule H-2Kb . After introduction them in zigotes we have obtained transgenic mouse strains, which could be used for modeling of interactions between tumor cells and immune system of recipient. Normally, B10. D2 (R101) mice reject lymphoma EL4 cells in 12–14 days after transplantation, in spite of the fact, that allogeneic difference between B10. D2 (R101) (Kd Id Db ) mice and lymphoma EL4 (H-2b) cells is only in one product of MHC, the H-2Kb molecule. Transgenics carrying β-chains of TCR displayed compromised immunity to tumor cells resulting to their long persistence, tumor progression, the loss of H-2Kb molecule and death in 2–3 months after transplantation. This model allows to see all three phases of interaction between tumor and immune system of recipient – elimination, equilibrium and escape. Against, transgenics carrying α-chain reject tumor cells much more quickly, as in secondary immune response, in 3–6 days after transplantation. This rejection was mediated by intraepithelial T lymphocytes displaying features of resident memory cells – inability to recirculation, expression of CD103 and early activation antigen CD69 and intermediate density of T-cell markers CD3 and CD8. The capability to be located in nonlymphoid tissue and quickly destroy tumor cells makes them to be the most probable candidate to perform immunological surveillance functions.